Learning Cities - Balázs Németh (Universidade de Lisboa, 2019)
This paper will analyse the conceptual evolution and development of learning cities and regions in adult education research work. Adult education research has got a great potential to investigate concrete mechanisms of learning city-region constructions and to estimate the changing nature and structures of learning city-region models based on the examples of two learning cities, Cork in Ireland and Pécs in Hungary. Therefore, the paper tries to discover some major aspects of learning city-region models and different learning city-region collaborations at local-regional levels, emphasized by the OECD and UNESCO, which may enhance both participation and performance in learning of adults, but also, the learning of other age groups affecting transgenerational dimensions of learning and that of community development.